DONOR KIR3DL1/RECEPTOR HLA-BW4-80I COMBINATION REDUCES ACUTE LEUKEMIA RELAPSE AFTER UMBILICAL CORD BLOOD TRANSPLANTATION WITHOUT IN VITRO T-CELL DEPLETION - xinchen fang; Zimin Sun; Huilan Liu; Xiang Wan; Wen Yao; Kaidi Song; Kaidi Song; Baolin Tang; Xiaoyu zhu; Jun Peng (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Donor natural killer (NK) cell alloreactivity in umbilical cord bone marrow transplantation (UCBT) can lead to leukemic relapse. However, NK cell function is calibrated by interaction with human leukocyte antigens (HLAs). This study aimed to investigate graft-resistant leukemia after transplantation and compared specific genotypes of killer immunoglobulin-like receptors (KIRs) in donors and human leukocyte antigen ligands in patients.